Directions for improvement of land use administration with consideration of environmental safety requirements - Kupriyanchyk І.; Svyrydova, L. (Land Management, Cadastre and Land Monitoring, 2019)
It is revealed that the general index of quality of state administration of land use in Ukraine is 15.5 points, which holds 76th place out of 186 states. It is revealed that its quality is determined by the coherence of the components of the administrative process: legal, regulatory, fiscal and information management. The essence of ecological and economic tools of land administration, which prompts landowners and land users to rational land use with financial, credit, fiscal, price, subsidy, control and other tools, is described in detail. It is determined that land protection activities should be financed from the state budget, from the profit of economic entities, from environmental, economic and insurance funds, provision of bank loans. In order to increase the responsibility of landowners and land users for compliance with ecological requirements in economic activity, introduction of land management regulations and economic sanctions is proposed. Areas of improvement of administration of land use taking into account the requirements of ecological safety are given. Key words: ecological and economic instruments, land use administration, economic stimulation, ecological safety